Characterization and Genome Analysis of the First Facultatively Alkaliphilic Thermodesulfovibrio Isolated from the Deep Terrestrial Subsurface - Frank, Yulia A.; Kadnikov, Vitaly V.; Lukina, Anastasia P.; Banks, David; Beletsky, Alexey V.; Mardanov, Andrey V.; Sen’kina, Elena I.; Avakyan, Marat R.; Karnachuk, Olga V.; Ravin, Nikolai V. (Frontiers in Microbiology, 2016)
Members of the genus Thermodesulfovibrio belong to the Nitrospirae phylum and all isolates characterized to date are neutrophiles. They have been isolated from terrestrial hot springs and thermophilic methanogenic anaerobic sludges. Their molecular signatures have, however, also been detected in deep subsurface. The purpose of this study was to characterize and analyze the genome of a newly isolated, facultatively alkaliphilic Thermodesulfovibrio from a 2 km deep aquifer system in Western Siberia, Russia. The new isolate, designated N1, grows optimally at pH 8.5 and at 65°C. It is able to reduce sulfate, thiosulfate or sulfite with a limited range of electron donors, such as formate, pyruvate, and lactate. Analysis of the 1.93 Mb draft genome of strain N1 revealed that it contains a set of genes for dissimilatory sulfate reduction, including sulfate adenyltransferase, adenosine-5′-phosphosulfate reductase AprAB, membrane-bound electron transfer complex QmoABC, dissimilatory sulfite reductase DsrABC, and sulfite reductase-associated electron transfer complex DsrMKJOP. Hydrogen turnover is enabled by soluble cytoplasmic, membrane-linked, and soluble periplasmic hydrogenases. The use of thiosulfate as an electron acceptor is enabled by a membrane-linked molybdopterin oxidoreductase. The N1 requirement for organic carbon sources corresponds to the lack of the autotrophic C1-fixation pathways. Comparative analysis of the genomes of Thermodesulfovibrio (T. yellowstonii, T. islandicus, T. àggregans, T. thiophilus, and strain N1) revealed a low overall genetic diversity and several adaptive traits. Consistent with an alkaliphilic lifestyle, a multisubunit Na+/H+ antiporter of the Mnh family is encoded in the Thermodesulfovibrio strain N1 genome. Nitrogenase genes were found in T. yellowstonii, T. aggregans, and T. islandicus, nitrate reductase in T. islandicus, and cellulose synthetase in T. aggregans and strain N1. Overall, our results provide genomic insights into metabolism of the Thermodesulfovibrio lineage in microbial communities of the deep subsurface biosphere.